Evolution of a Schmorl's Node and a Degenerative Osteophyte on Sequential 68Ga-DOTATATE PET/CT Scans: Potential Pitfalls in Neuroendocrine Tumor Imaging. (January 2019) - Hod, Nir; Levin, Daniel; Anconina, Reut; Benkovich, Elya; Ezroh Kazap, Dina; Lantsberg, Sophie
Abstract : Abstract: Schmorl's node (SN) arises from the herniation of the nucleus pulposus of the disc through the cartilaginous endplate into the body of the vertebra. Our report describes a patient with carcinoid tumor who underwent a series of 68 Ga-DOTATATE PET/CT scans for follow-up, demonstrating gradually increasing focal vertebral uptake in absence of CT abnormality, suspicious for a metastasis. Both CT and MRI eventually revealed classical findings of a SN. Also observed in the same vertebra is a degenerative osteophyte showing intense 68 Ga-DOTATATE uptake. This interesting case shows 2 benign spinal lesions, which potentially can simulate bone metastasis in patients with neuroendocrine tumors.